Trade relations of the EEC : an empirical investigation - Kreinin, Mordechai Elihau (New York : Praeger, 1974)
This volume brings together several empirical studies concerning the international trade relations of the European Economic Community (EEC).
Includes bibliographical references.
ne 21/01/2019
Loans
Keywords: Commerce; Commercial policy; European Economic Community countries